Aporte que se está dejando de recibir por trabajadores en capacidad de cotizar que no lo hacen (2017)
Colombia is a country with low coverage in the pension system. Currently, the employed population is 28,683,259 people. Within this group, only 7.7 million individuals are affiliated to this system, which implies that the rest of the employed people are not listed or have alternative methods of saving, but what is the effect of this lack of coverage? This paper seeks to find the gap between the net collection and what should have been collected from 2009 to 2016, given the number of employed in the country. This aims to find the value and thus quantify the impact generated by the lack of affiliation to the pension system.